Kinetics of Sulfide Removal in Biofilter Employing Sulfur-Oxidizing Bacteria on Salak Fruit Seeds - Lestari, Retno Ambarwati Sigit; Sediawan, Wahyudi Budi; Sarto, Sarto (Jurnal Bahan Alam Terbarukan, 2019)
Sulfur-oxidizing bacterias were isolated then grown on salak fruit seeds forming bio-film. Their performances in sulfide removal were experimentally observed. The salak fruit seeds were then used as packing material in a cylinder. Liquid containing 83 ppm of sodium sulfide was flown through the bed. Then the sulfide concentrations in the outlet at various times were analyzed. A set of simple kinetics model for the rate of the sulfide removal and the bacterial growth was proposed. The axial sulfide concentration gradient in the flowing liquid are assumed to be quasi-steady-state. Mean while the bio-film grows on the surface of the seeds and the sulfide oxidation takes place in the bio-film. Since the bio-film is very thin, the sulfide concentration in the bio-film is assumed to be uniform. The simultaneous ordinary differential equations obtained were then solved numerically using Runge-Kutta method. The accuracy of the model proposed was tested by comparing the calculation results using the model with the experimental data obtained. It turned out that the model proposed can be applied to quantitatively describe the removal of sulfide in liquid using bio-filter in packed bed. The values of the parameters were also obtained by curve-fitting.